CANINE HEARTWORM DISEASE IN A BRAZILIAN NON-ENDEMIC AREA - Monobe, Marina Mitie; Silva, Rodrigo Costa da; Melanchauski, Mariana Serrano; Lopes, Raimundo Souza (Arquivos de Ciências Veterinárias e Zoologia da UNIPAR, 2016)
Canine Heartworm Disease (CHD) is a mosquito-borne disease caused by Dirofilaria immitis. In this study, two mature adult-senior dogs from a non-endemic area to CHD presented clinical signs suggestive to the disease. The first one presented skin lesions, loss of appetite, weakness, pale mucosa membrane, and hyperthermia, whereas the second one presented severe ascites, anorexia and exercise intolerance, lateral decumbency, and marked heart murmurs. Both presented tachypnea, thrombocytopenia, leukocytosis, and microfilaremia. Multiplex-PCR (COI gene) resulted positive to D. immitis research in both cases, confirmed by sequencing, with 98% homology to D. immitis (Gen Bank accession n.AJ537512-1). In addition, both animals have never had any prophylactic treatment to CHD, and no reports about traveling to coastal areas. This study reported two unusual cases of D. immitis infection in non-endemic area from Brazil.